5x+6-3x-3=6

Simple and best practice solution for 5x+6-3x-3=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+6-3x-3=6 equation:


Simplifying
5x + 6 + -3x + -3 = 6

Reorder the terms:
6 + -3 + 5x + -3x = 6

Combine like terms: 6 + -3 = 3
3 + 5x + -3x = 6

Combine like terms: 5x + -3x = 2x
3 + 2x = 6

Solving
3 + 2x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 2x = 6 + -3

Combine like terms: 3 + -3 = 0
0 + 2x = 6 + -3
2x = 6 + -3

Combine like terms: 6 + -3 = 3
2x = 3

Divide each side by '2'.
x = 1.5

Simplifying
x = 1.5

See similar equations:

| 7(2a-4b)-3(4a-2b)= | | P+30.34= | | 3x^2-6x+4=13 | | 6x+3(2x+8)=120 | | 8x=2+y | | (22b-1)-7(3b+3)=-6 | | 5x(2x^2-3x+3)= | | C=15s+75 | | =90-70 | | 2y^2-y-36=0 | | 2x+25=3 | | 8x(9x+5)= | | 6s-17=-8+3s | | x*87=87 | | 3k+15-9=2(1k+2) | | 6r-15=0+r | | 5x-3(x-1)=7 | | 7-3x+5when=2 | | x(x+40)=180 | | 6p+5[3(2-3p)-2(5-4p)]= | | -42=7(8-x) | | (3x-5)+(6x-40)=90 | | (3x-5)+(6x-40)= | | -7x+10=10-7x | | 4a^2-17a-15=0 | | -5y^2+8y+7=0 | | 45/6b+4111/140=4/5b-22/5+11/7 | | 8x(9x)= | | x=(x+40) | | =2+2sin(i) | | 3(2m-1)+9=6(1m+1) | | 12+9g=93 |

Equations solver categories